2022
DOI: 10.1038/s41523-022-00476-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunologically “cold” triple negative breast cancers engraft at a higher rate in patient derived xenografts

Abstract: TNBC is a heterogeneous subtype of breast cancer, and only a subset of TNBC can be established as PDXs. Here, we show that there is an engraftment bias toward TNBC with low levels of immune cell infiltration. Additionally, TNBC that failed to engraft show gene expression consistent with a cancer-promoting immunological state, leading us to hypothesize that the immunological state of the tumor and possibly the state of the immune system of the host may be essential for engraftment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…One assumption of previous PDX studies has been that the success or failure of a single tumour region represents the behaviour of the tumour overall. However, we find that distinct spatial regions of the same tumour can have divergent outcomes in PDX models, and that engraftment is correlated with tumour purity and inversely associated with T cell infiltration, consistent with a study of breast cancer PDX models 37 . Prior studies also suggest that lung squamous carcinomas more readily give rise to PDX than lung adenocarcinomas [16][17][18][19] .…”
Section: Discussionsupporting
confidence: 90%
“…One assumption of previous PDX studies has been that the success or failure of a single tumour region represents the behaviour of the tumour overall. However, we find that distinct spatial regions of the same tumour can have divergent outcomes in PDX models, and that engraftment is correlated with tumour purity and inversely associated with T cell infiltration, consistent with a study of breast cancer PDX models 37 . Prior studies also suggest that lung squamous carcinomas more readily give rise to PDX than lung adenocarcinomas [16][17][18][19] .…”
Section: Discussionsupporting
confidence: 90%
“…As shown in Figure 6D, both CD4 + T cells and CD8 + T cells were scarcely detected in the control group, indicating that TNBC represents an immune “cold” tumor with minimal T cell infiltration. [ 35,36 ] Conversely, all treatment groups displayed a marked increase in T cell infiltration, with the aPD‐1/PTX NPs@MNs group registering the highest infiltration. Immunofluorescence staining for CD8 + T cells yielded congruent findings (Figure S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…C1P levels are not significantly different in tumor tissue than normal tissues, although some studies have shown higher C1P/CERK levels in lung or pancreatic cancer cells and lower in oral squamous cell carcinoma 44,45 . As C1P is known to cause inflammation, lower C1P levels in TNBC tissues as compared to luminal tissue can be correlated to its “COLD” immunosuppressive nature due to poor infiltration of immune cells specially CD3 and CD8 T cell types 46 . Therefore, role of C1P in proliferation, inflammation, and metastasis depends on cancer cell type and context.…”
Section: Discussionmentioning
confidence: 99%
“…immunosuppressive nature due to poor infiltration of immune cells specially CD3 and CD8 T cell types. 46 Therefore, role of C1P in proliferation, inflammation, and metastasis depends on cancer cell type and context. Different chain-length ceramides have been shown to exert opposing effects in various cancer models where decrease in ceramide synthesis through sphingomyelin hydrolysis inhibited tumor growth.…”
Section: Discussionmentioning
confidence: 99%